Evaluation of steering grip strength among drivers during driving proton's car / Mohd Hafiz Ridha Hassim - Hassim, Mohd Hafiz Ridha (2010)
The evaluation of steering wheel grip strength among drivers may benefit to automobile designers and manufacturers to improve the quality of their product in terms of comfort and driving performance. This project is to evaluate the steering wheel grip strength among drivers during driving proton's car between male and female under varying speed (50km/h and 80km/h). 10 subjects were participating in this project including 5 males and 5 females. The measurements were made by using electromyography (EMG and the data obtained were compared between male driver and female driver under different variance of speed. The different vehicle speed on the road shows significant different values that affect drivers. From this experiment, factors that contribute to the grip strength variances also have been determined. At the lower speed, pressure from the higher speed car is one of the factors of variances grip strength of the drivers. The different height of every person also affects the result.